Laboratory testing for antiphospholipid syndrome. (9th May 2016) - Pengo, V.; Banzato, A.; Bison, E.; Denas, G.; Zoppellaro, G.; Bracco, A.; Padayattil Jose, S.; Hoxha, A.; Ruffatti, A.
Summary: This is a practical report on laboratory tests for the diagnosis of antiphospholipid syndrome (APS). After a general definition of APS, this study deals with appropriateness and timing in requesting the determination of antiphospholipid (aPL) antibodies. Lupus anticoagulant (LAC), anticardiolipin (aCL), and anti β2‐glycoprotein I (aβGPI) are the mandatory tests to be performed, while other tests are not yet validated for clinical use. Interpretation of results is an important discussed issue that implies a close liaison between clinical pathologists and clinicians. Finally, a personal definition of APS according to aPL antibody profile closes the manuscript.